FENOMENA STOP BAYAR PAJAK DI MEDIA SOSIAL SEBAGAI EKSPRESI KEKECEWAAN MASYARAKAT TERHADAP DISTRIBUSI DAN TATA KELOLA HASIL PAJAK: SUATU TINJAUAN HUKUM NORMATIF DAN SOSIOLOGIS - Agnes Angelika; Naira Puspita; Keyza Naila Humaira Hermana; Sela Amanatul Fatiha; Moh. Imam Gusthomi (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The emergence of the "stop paying taxes" movement on social media social phenomenon reflecting the decline of public trust in the government's management and distribution of tax revenues. This study aims to analyze the phenomenon from normative legal and sociological perspectives in order to understand its underlying causes and its implications for the relationship between the state and its citizens. This normative legal research employs conceptual, statutory, and sociological approaches through literature review of relevant legislation, legal theories, academic literature, and social data. The findings indicate that the emergence of the stop paying taxes movement should not be understood merely as an act of legal disobedience, but rather as an expression of public dissatisfaction with development disparities, weak transparency in budget management, corruption practices, and the suboptimal distribution of tax benefits to society. From the perspectives of social contract theory and state legitimacy theory, declining public trust has the potential to undermine tax compliance, which has long served as a fundamental pillar of state revenue. Nevertheless, the obligation to pay taxes remains constitutionally binding and therefore cannot be unilaterally rejected. Consequently, reforms in tax governance, enhanced accountability and transparency, and more equitable development policies are necessary to restore public trust and strengthen the legitimacy of the national taxation system.